IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PELESTARIAN KAWASAN HUTAN MANGROVE DI KABUPATEN POHUWATO - Sudarmono Sompah (Publik : (Jurnal Ilmu Administrasi), 2015)
The aim of this research was to look at the implementation of government policies in the conservation of mangrove in Pohuwato regency. This research method using a case study explanative approach. Through the process of collecting data through observation, interviews and documentation, the data processed by reducing the data and then presented to provide an overview of policy implementation by local governments. Based on the results of the research, the percentage of the evaluation context (policy) found 95% categorized as very good, the evaluation of inputs (resources) found 96.4% categorized as very good, the evaluation process (implementation) found 90% categorized as very good, product evaluation (impact) found 75% categorized quite good. Then, from each of these results concluded that 93.3% considered excellent training program. In the implementation of the policy there are several factors that influence in the preservation of mangrove forest that is communication, bureaucratic structure, availability of resources that has to do with the funds, facilities and infrastructure advice and disposition factors as the attitude of the executive to implement the policy.